2014
DOI: 10.1002/ece3.1202
|View full text |Cite
|
Sign up to set email alerts
|

The aging biological clock in Neurospora crassa

Abstract: The biological clock affects aging through ras-1 (bd) and lag-1, and these two longevity genes together affect a clock phenotype and the clock oscillator in Neurospora crassa. Using an automated cell-counting technique for measuring conidial longevity, we show that the clock-associated genes lag-1 and ras-1 (bd) are true chronological longevity genes. For example, wild type (WT) has an estimated median life span of 24 days, while the double mutant lag-1, ras-1 (bd) has an estimated median life span of 120 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 52 publications
(132 reference statements)
3
34
0
1
Order By: Relevance
“…Our previous publication revealed that the longevity assurance gene ( lag‐1 ), a gene encoding a ceramide synthase, not only is a longevity gene but also exerts control over the biological clock in the model organism Neurospora crassa (Case et al., 2014). Circadian rhythms and biological clocks play important roles in diverse cellular processes across the tree of life (Bell‐Pederson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous publication revealed that the longevity assurance gene ( lag‐1 ), a gene encoding a ceramide synthase, not only is a longevity gene but also exerts control over the biological clock in the model organism Neurospora crassa (Case et al., 2014). Circadian rhythms and biological clocks play important roles in diverse cellular processes across the tree of life (Bell‐Pederson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the organismal level, transcriptomic studies using microarray technologies have shown that nearly twenty‐five percent of the genes in the N. crassa have a circadian response, revealing that the biological clock has evolved as an important mechanism for controlling many biochemical processes (Dong et al., 2008). These same transcriptional studies revealed a transient response in transcription levels of lag‐1 under knockdown of white collar‐1 ( wc‐1) , an important N. crassa clock gene (Case et al., 2014). These findings spurred our interest in studying the longevity and clock effects of lag‐1 knockouts, along with our current study on knockouts of the lag‐1 paralog, longevity assurance cognate‐1 ( lac‐1 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations